2006
DOI: 10.1177/070674370605100608
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance and Adiponectin Levels in Drug-Free Patients with Schizophrenia: A Preliminary Report

Abstract: Objective: To compare the insulin sensitivity and adiponectin levels of medication-free patients suffering from schizophrenia or schizoaffective disorder with that of matched healthy volunteers. Method: We evaluated 9 nondiabetic patients aged 26.6 years (median 26 years, range 17 to 41 years) and matched volunteers, using the frequently sampled intravenous glucose tolerance test, minimal model analysis, and fasting adiponectin levels. Results: The mean insulin sensitivity index of the patients was 42% lower t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
62
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(70 citation statements)
references
References 12 publications
7
62
0
1
Order By: Relevance
“…There is a body of evidence to suggest that schizophrenia itself may be linked to an increased risk of glucose dysregulation, although the data remain contradictory on this point. [46][47][48][49][50] More consistent are the findings that, at least prior to the onset of FEP, schizophrenia is not associated with increased risk of obesity. [48][49][50][51][52][53] Indeed, several reports have suggested that an FEP is associated with lower BMI values than seen in control subjects.…”
Section: The Association Between Schizophrenia and Obesitysupporting
confidence: 54%
“…There is a body of evidence to suggest that schizophrenia itself may be linked to an increased risk of glucose dysregulation, although the data remain contradictory on this point. [46][47][48][49][50] More consistent are the findings that, at least prior to the onset of FEP, schizophrenia is not associated with increased risk of obesity. [48][49][50][51][52][53] Indeed, several reports have suggested that an FEP is associated with lower BMI values than seen in control subjects.…”
Section: The Association Between Schizophrenia and Obesitysupporting
confidence: 54%
“…These proinflammatory agents are thought to induce oxidative stress thereby exacerbating underlying pathological processes leading to dyslipidemia, glucose intolerance, insulin resistance, and endothelial dysfunction that are common in obesity and type II diabetes mellitus (T2DM) (Sonnenberg et al, 2004). Previous cross-sectional studies found both higher (Togo et al, 2004) and lower (Richards et al, 2006) adiponectin levels in patients treated with olanzapine compared to healthy controls as well as lower levels in untreated patients compared to controls (Cohn et al, 2006). One additional study found no change in adiponectin after 4 weeks of olanzapine treatment (Hosojima et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Some [5][6][7][8] but not all 9 studies have found that compared with matched controls, newly diagnosed, antipsychoticnaive patients with nonaffective psychosis have an increased prevalence of impaired glucose tolerance, diabetes, or increased insulin resistance. This conclusion is far uncertain because some of these studies were weakened by problems in matching or possible confounding by hypercortisolemia.…”
mentioning
confidence: 99%